A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna) - Wilson, Lyle; Channing, Alan (Zootaxa, 2019)
Tomopterna branchi sp. nov. is described from Namaqualand, South Africa. It differs from all other Tomopterna species by advertisement call, 16S rRNA sequence and consistent differences in adult morphology. The tadpole is similar to that of Tomopterna cryptotis. Haplotype networks of 16S and the nuclear tyr gene show that it is distinct from T. delalandii, with which it has been confused. A phylogeny of the genus, excluding the little-known T. monticola, shows that the new species is basal to a clade that includes T. delalandii and six other species. We extend the known range of T. damarensis to southern Namibia, and correct the identification of some GenBank material.